Fast-Tracking the Resolution of Minor Disputes : Experience from EU Member States - Harley, Georgia; Said, Agnes (World Bank, Washington, DC, 2017)
The costs and long duration of court proceedings can be discouraging, and for the poor and micro and small enterprises (MSMEs) it can preclude access to justice entirely. According to the latest CEPEJ data, in 2014 disposition time of first instance civil and commercial litigious cases ranged from 97 days in Lithuania to 532 in Italy, with an overall EU average of 250 days.2 Costs (comprising both lawyer and court fees) can sometimes be greater than the value of the claim. Legislators around the world have long recognized that disputes concerning smaller claims may not require the same complex procedures and rules; instead, they can be resolved in a cheaper and more efficient manner. Although small claims procedure is not a new phenomenon and has existed for decades, it has only recently gained traction. Factors such as popular demand spur more and more countries into looking for new and faster ways to deal with smaller claims, as citizens are looking for simpler, ICT-enabled ways to resolve smaller disputes. This report provides a comparative analysis of small claims procedure in the 28 EU Member States, including lessons learned and good practices, to inform EU members and candidate countries looking to introduce or reform their small claims procedure. It considers a number of dimensions, namely: court fees, thresholds, institutional set-up, use of technology, the role of lawyers, lawyer fees, and avenues of appeal.